2022
DOI: 10.1002/aenm.202202432
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport Kinetics in Low‐Temperature Lithium Metal Batteries

Abstract: The deployment of rechargeable batteries is crucial for the operation of advanced portable electronics and electric vehicles under harsh environment. However, commercial lithium‐ion batteries using ethylene carbonate electrolytes suffer from severe loss in cell energy density at extremely low temperature. Lithium metal batteries (LMBs), which use Li metal as anode rather than graphite, are expected to push the baseline energy density of low‐temperature devices at the cell level. Albeit promising, the kinetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 140 publications
2
66
0
Order By: Relevance
“…Low ambient temperature causes a significant cell resistance and polarization, leading to a lower state of charge (SOC, defined in %, where 100% means the maximum number of Li + that can be fully reversibly intercalated or de-intercalated in the applied voltage region) of electrodes, and causing a significant decrease of the capacity and faster degradation upon continuous cycling [28,29]. The increased resistance at low temperatures is believed to be mainly associated with the changed migration behavior of Li + at each battery component, including electrolyte, electrodes, and electrode-electrolyte interphases [21,26]. Being a Li + conducting medium, high-freezing-point electrolyte remains the main rate-limiting factor for different LIB systems at low temperatures.…”
Section: Essential Problems Affecting the Lib Performance At Low Temp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Low ambient temperature causes a significant cell resistance and polarization, leading to a lower state of charge (SOC, defined in %, where 100% means the maximum number of Li + that can be fully reversibly intercalated or de-intercalated in the applied voltage region) of electrodes, and causing a significant decrease of the capacity and faster degradation upon continuous cycling [28,29]. The increased resistance at low temperatures is believed to be mainly associated with the changed migration behavior of Li + at each battery component, including electrolyte, electrodes, and electrode-electrolyte interphases [21,26]. Being a Li + conducting medium, high-freezing-point electrolyte remains the main rate-limiting factor for different LIB systems at low temperatures.…”
Section: Essential Problems Affecting the Lib Performance At Low Temp...mentioning
confidence: 99%
“…Piao et al focused more on heating techniques and thermal management to control the external reaction temperature [21]. The most recent reviews dissected the Li + transport/diffusion in electrolyte, solid electrode and their interphase, temperature-dependent limitating factors and challenges of lithium batteries, and offered their strategies to make an improvement [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The speed of ion transport in the interfacial layer is the key to uniform deposition, which affects the overall performance of Zn metal anode. [18] Some studies have shown that dendrite growth is inhibited when electrolytes with higher ionic conductivity and higher migration number are used. [15a,19] Uneven deposition is the beginning of a vicious cycle and dendrites growth.…”
Section: Principle I: Fast Ion Conduction Uniform Ion Fluxmentioning
confidence: 99%
“…The implementation of small amount of FEC in the solvation structure increases ion carrier concentration and Li + transport channels in the SEI, as creating more inorganic compounds and grain boundaries [2b,14] . Therefore, sufficient Li + flux in the bulk electrolyte and fast charge‐transfer in the SEI, being inherent in this electrolyte design, are effective to resolve the low‐temperature limiting factor of the LMA [5a,10] . With these properties of our LHCE, the LMA could obtain substantially improved Li deposition morphology and plating/stripping stability from room temperature (RT) to −40 °C.…”
Section: Introductionmentioning
confidence: 99%